ENHANCING LEARNING PARTICIPATION OF INTERNATIONAL STUDENTS IN THE CLASSROOM USING SOCIAL MEDIA: THE CASE OF INTERNATIONAL STUDENTS IN THE UK UNIVERSITY - Aziz, Subkhi Abdul (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2022)
The utilisation of social media for education such as Kahoot! and Padlet to improve the classroom learning experience has become popular in recent years. This study investigates the implementation of Kahoot! and Padlet in the international students' learning environment at the UK university. The purpose of this study was to explore international students' perspective towards the implementation of Kahoot! and Padlet in the classroom learning process. In doing so, this study used a qualitative research design. Data were collected from ten international students from six different countries origin via semi-structured interviews. The results suggest that the implementation of Kahoot! and Padlet can improve the classroom learning process and create better study experience than the conventional way. Several benefits have been identified from the implementation of Kahoot! and Padlet in the international students learning environment, such as managing classroom discussion, building up an active classroom discussion, and encouraging critical thinking. However, some challenges regarding the implementation should be considered, notably those related to technical matters and the production of interesting contents. From this study, it can be concluded that using social media applications, such as Kahoot! and Padlet, can enhance students’ collaboration learning as well as support an inclusive classroom learning environment.